PENGARUH PENERIMAAN PAJAK HIBURAN DAN PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH - Halomoan Sihombing (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2020)
This research was conducted to examine the effect of Entertainment Tax Revenue, Billboard Tax on Local Revenue. This research is a quantitative study that is research data in the form of numbers or qualitative data called scoring. The data used in this study were obtained from the Medan City Regional Tax and Retribution Management Agency from 2011 to 2018. The method used in this study is multiple regression analysis. The results obtained indicate that the Entertainment Tax has a positive and significant effect on the Original Revenue of Medan City. Advertisement tax has a positive but not significant effect on Medan's Original Local Revenue. Simultaneously the Entertainment Tax and Advertising Tax significantly influence the original income of the city of Medan. Keywords: Entertainment Tax, Advertisement Tax, Local Revenue